Peningkatan Kualitas Produksi Garam Menggunakan Teknologi Geomembran - Yuliana Ulfidatul Hoiriyah (Trunojoyo University of Madura, 2019)
Salt is a very important commodity in daily life, both for food and industrial needs. Therefore, increasing salt production is very necessary to meet domestic salt needs. One of the most salt producing regions is Madura Island, because almost every district, especially Pamekasan, Lembung, Kec. Galis, the majority of the population work as salt farmers. The purpose of this research is to find out about improving the quality of salt production in Lembung, Kec. Pamekasan Regency, Madura, East Java Province. using Geomembrane Technology. This research is a descriptive qualitative research. The sample of this research is a resident who works as a salt farmer in the village of Lembung, Galis Regency, Pamekasan Regency, East Java, this sampling technique uses the Purposive Sampling method, data collection is done through interview session techniques, and documentation. Based on this research, it can be concluded that the increase in the quality of salt production can be done by using geomembrane technology which significantly influences the quality and quantity of production.